Investigação da potencialidade melancólica em adolescentes - Raslan, Rodrigo Vasconcelos (2007)
The present study consists of the investigation, elaboration and development of the concept of Melancholic Potentiality through presupposed theoretical, as well as, starting from a case study accomplished to an adolescent, being this in execution of social-educational measure of internment. From the theoretical/conceptual point of view, the Psychoanalysis, while therapeutic technique, theory of the psyche and method of investigation of the unconscious, was the used referential, especially the work of Aulagnier, Freud and Violante. The relevance and the clinical usefulness and/or social of that research is justified in the measure in that, the concept of Melancholic Potentiality, while diagnostic hypothesis, can guide, from the ethical and technical point of view of the analyst listening and of other professionals that are devoted to the clinical praxis